Science Flipbook Media on Elementary School Students' Learning Outcomes - Rima Devita Sari; Ana Fitrotun Nisa; Akbar Al Masjid; Banun Havifah Cahyo Khosiyono (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to determine the effect of using flipbook media on improving student learning outcomes at Ngrenak State Elementary School on the topic of eating and being eaten by comparing the results of the pretest and posttest. The methodology used is a quantitative approach with a quasi-experimental type with descriptive analysis, normality test, homogeneity test, paired t-test to determine the variance of pretest and posttest data, simple linear regression test to determine the relationship between independent variables and dependent variables and N-Gain test to determine the effectiveness of flipbook media on science learning outcomes with the SPSS version 26 application. The population in this study were all fifth grade students of Ngrenak State Elementary School, totaling 31 students. The results showed that flipbook media had a significant effect on science learning outcomes of fifth grade students of Ngrenak State Elementary School by 79% on the topic of eating and being eaten. Based on the N-Gain test, the level of effectiveness of using flipbook media in improving science learning outcomes was 49%.